Decentralized multi-agent formation control with pole-region placement via cone-complementarity linearization - González, Antonio; Sala, Antonio; Armesto, Leopoldo (Zielona Góra: Uniwersytet Zielonogórski)
An output-feedback decentralised formation control strategy is pursued under pole-region constraints, assuming that the agents have access to relative position measurements with respect to a set of neighbors in a graph describing the sensing topology. No communication between the agents is assumed; however, a shared one-way communication channel with a pilot is needed for steering tasks. Each agent has a separate copy of the same controller.
Keywords: multi-agent autonomous system; formation control; decoupling; linear matrix inequalities; cone-complementarity linearization